Application of sequential factorial design and orthogonal array composite design (OACD) to study combination of 5 prostate cancer drugs. (April 2017) - Jia, Xiaolong; Li, Yiyang; Sharma, Alok; Li, Yulong; Xie, Guohai; Wang, Guoyao; Jiang, Junhui; Cheng, Yue; Ding, Xianting
Graphical abstract: Highlights: A sequential application of two-level and orthogonal array composite design was introduced. Optimization of 5 selected anti-prostate-cancer drugs were studied. Doxorubicin and docetaxel were found most significant and effective combinations in the cancer survival model used in the study. Present work illustrate for better understanding of anti-cancer drug mechanism that can facilitate clinical practice of better drug combination. Abstract: Prostate cancer is one of the most common cancers among men in the United States. It is also a major leading cause of cancer death among men of all races. In order to treat prostate cancer, drug combinations are often applied. Drug combinations target at different pathways of cells can potentially lead to higher efficacy and lower toxicity due to drug synergy. In this paper, we sequentially applied a two-level design and a follow-up orthogonal array composite design (OACD) to investigate combinations of five anti-cancer drugs, namely, doxorubicin, docetaxel, paclitaxel, cis -dichlorodiamine platinum and dihydroartemisinin. Our initial screening using a two-level full factorial design identified doxorubicin and docetaxel as the most significant drugs. A follow-up experiment with an OACD revealed more complicated drug interactions among these 5 anti-cancer drugs. Quadratic effects of doxorubicin and paclitaxel appeared to be significant. A further investigation on contour plots of all the two-drug pairs indicated that combination of doxorubicin and docetaxel are the most effective companion, while the combination of cis -dichlorodiamine platinum and dihydroartemisinin showed unknown antagonistic effects which diminished the individual drug anti-cancer efficacy. These observations have significant practical implications in the understanding of anti-cancer drug mechanism that can facilitate clinical practice of better drug combinations.